Management of Selected Competences During Education of Manager and Leader in Public Services - Bartosz SYLWESTRZAK (Communications of International Proceedings, 2022)
Challenges caused by recent disorders and crises of military and non-military nature in the modern world force an innovative and somewhat different approach to personnel management in state services responsible for public order, national rescue and security. Managers and commanders in these services, especially those in charge of human teams, should be characterized by certain qualifications and competences in relation not only to the tasks they carry out but also in relation to the expectations and attitudes of the rest of the society since repeatedly the tasks performed are carried out in cooperation with citizens. However, changes in various social groups, professional mobility, mixing of cultures and traditions mean that current solutions for training and preparation of leaders and managers to manage human teams in such services should be thoroughly analyzed and supplemented with new concepts arising from social needs and expectations.
Keywords: leader’s competences; public service; education.